2002
DOI: 10.1111/j.1572-0241.2002.05434.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to clinical manifestations in familial adenomatous polyposis with special reference to duodenal lesions

Abstract: Truncating APC gene mutation proximal to exon 9 may contribute to the less frequent development of duodenal adenomatosis in FAP, but severity and progression of duodenal adenomatosis do not seem to be determined by APC gene mutation alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 36 publications
3
30
0
1
Order By: Relevance
“…13 Furthermore, the development of FGP was independent of the site of germline APC mutation. 12 These observations were confirmed in the present investigation. Furthermore, we could demonstrate that the contribution of SNP in PLA2g2a to the development of FGP remained to be significant even when H. pylori infection was taken into consideration.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…13 Furthermore, the development of FGP was independent of the site of germline APC mutation. 12 These observations were confirmed in the present investigation. Furthermore, we could demonstrate that the contribution of SNP in PLA2g2a to the development of FGP remained to be significant even when H. pylori infection was taken into consideration.…”
Section: Discussionsupporting
confidence: 93%
“…[15][16][17][18][19][20][21][22][23] Although it should be noted that PTT applied in our study does not detect all mutations of APC and in fact the method missed 5 percent of APC mutation, we have previously shown a genotypephenotype correlation in Japanese patients with FAP by means of PTT. 12,24 We performed direct sequence for 37 of 55 patients; 10 of 37 patients were negative for PTT: 1 of the 10 patients with negative PTT had a missense mutation (data not shown). Among the ten patients with negative PTT result, direct sequence identified a missense mutation in one patient, whereas APC mutation remained undetermined in the other nine patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In our study, advanced duodenal aVection and death of duodenal cancer were reported in 18 unrelated families with mutations spanning from codon 213 through codon 1,464. This is a relatively high frequency indicating that risk of duodenal adenomas is likely to be inXuenced by factors additional to APC, as have been suggested by others (Enomoto et al 2000;Matsumoto et al 2002).…”
Section: Genotype-phenotype Correlationmentioning
confidence: 73%